Phylogenetic Analysis of Polyporous Fungi Collected from Batam Botanical Garden, Riau Province, Indonesia - Anis Sri Lestari; Deni Zulfiana; Apriwi Zulfitri; Ni Putu Ratna Ayu Krishanti; Titik Kartika (Biosaintifika: Journal of Biology & Biology Education, 2018)
Botanical gardens are areas that provide protection for trees and other organisms like polyporous fungi. Polyporous fungi are important fungi that degrade remaining lignocellulosic in leaf litter or dead trees. These mycobiota are also noted for their vital role in biorefinery, bioremediation, medicine and phytopathogen. The knowledge of the importance of the polyporous fungi to describe polyporous fungal species is fundamental for generating data base information of their occurrence and their functions. This research’s goal was to explore and characterize the polyporous fungi collected in Batam Botanical Garden in three sampling areas. Fungal samples were collected in May and July 2017. Subsequently, morphological characters were recorded, the fungal tissue was isolated to extract the DNA, then the data sequence was amplified and aligned to construct a phylogenetic tree. Five fungal families found belong to order Polyporales and were classified morphologically. They were Polyporaceae, Ganodermataceae, Fomitopsidaceae, Irpicaceae and Hymenochaetaceae. Three fungal species namely; Pycnoporus sanguineus, Trametes ijubarskii, and Antrodia wangii were identified based on phyllogenetic analysis whereas seven other fungal samples were identified as Earliella scabrosa, Hexagonia tenuis, Polyporus tenuiculus Lenzites betulina, Lentinus concavus, Phellinus rimosus and Hexagonia apiaria. This study classifies and adds fundamental databases on fungal taxonomy and diversity on the fungal organisms found in Batam Botanical Garden. This background data is vital to carry out an advance research in some areas such as bio-chemistry, bio-degradation, pharmacology and biotechnology.